Aunting as a Call to Public Intellectualism: The Roles of (In)Visibility in Health Communication Research and Service. Issue 8 (3rd August 2017) - Tikkanen, Stephanie A.
ABSTRACT: In this essay, the author identifies the theme of (in)visibility permeating her research on fathers of children with a rare genetic condition, Sturge–Weber syndrome. The tension between physical visibility of the condition and lack of awareness is explored, alongside issues of (in)visibility in coping and support-seeking strategies of fathers. Finally, the author examines her own experiences in the research process through the lens of (in)visibility, in both managing her own emotions and exploring her roles as a researcher, an aunt, and a public intellectual.